Effects of Probiotic Bacillus as an Alternative of Antibiotics on Digestive Enzymes Activity and Intestinal Integrity of Piglets - Hu, Shenglan; Cao, Xuefang; Wu, Yanping; Mei, Xiaoqiang; Xu, Han; Wang, Yang; Zhang, Xiaoping; Gong, Li; Li, Weifen (Frontiers in Microbiology, 2018)
The previous study in our team found that supplementation of probiotic Bacillus amyloliquefaciens (Ba) instead of antibiotics growth performance of piglets. Hence, the present study was carried out to further demonstrate the effect of Ba replacement of antibiotics on digestive and absorption enzyme activity and intestinal microbiota population of piglets. A total of 90 piglets were selected and divided into three groups: G1 group was fed with basal diet supplemented with 150 mg/Kg aureomycin, G2 group was fed with 1 × 108 cfu/Kg Ba and half dose of aureomycin, G3 group was used the diet with 2 × 108 cfu/Kg Ba replaced aureomycin. Each treatment had three replications of ten pigs per pen. Results indicated that Ba replacement significantly increased the activities of amylase, disaccharides and Na+/K+-ATPase. And chymotrypsin activity in different section of intestine was dramatically enhanced in half replacement of aureomycin with Ba. Moreover, Ba replacement maintained the intestinal integrity with the significantly decreased activity of DAO compared with aureomycin group. Besides, supplementation with Ba increased the β-diversity of intestinal microbiota. Taken together, the current study indicated that diet supplementation with Ba instead of aureomycin increased the growth performance of piglets by improving the digestive and absorb enzyme activities, enhancing the intestinal integrity and regulating the population of intestinal micrbiota.